DEVELOPING AN INNOVATION STRATEGY FOR ENTERPRISES TO ENHANCE COMPETITIVENESS - Israilov Rustam Ibragimovich (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Objective: This study aims to explore the role of development strategies in enhancing organizational competitiveness amidst a rapidly changing environment, emphasizing the significance of an innovation-driven approach to achieving long-term sustainability. Methods: The research employs a qualitative analysis of market-driven strategic frameworks and their application within industries and sectors, emphasizing the integration of socially-oriented transformations and innovation strategies into organizational operations. Results: The findings indicate that adopting an innovation strategy significantly contributes to the growth of industries and sectors within the national economy. Organizations with a focus on sustainable innovation demonstrate improved adaptability to evolving market conditions and a stronger foundation for maintaining competitive advantages. Novelty: This study highlights the interplay between innovation strategies and socially-oriented transformations as pivotal for modern organizations. It underscores the dual role of innovation as both a driver of national economic growth and a tool for creating sustainable competitive advantages in a dynamic environment.